MO742: The Influence of Haemodialysis on Ultra-Sensitive and High Sensitive Troponin I—A Systematic Review. (3rd May 2022) - Kampmann, Jan; Mickley, Hans; Heaf, James; Hafsund, Marius; Mejer Hunderup, Michael; Backer Mogensen, Christian; Brandt, Frans
Abstract: BACKGROUND AND AIMS: Troponin is the preferred biomarker for diagnosing acute myocardial infarction (AMI). The new generations of high-sensitive troponin (hs-cTnI) assays are now the most commonly used including ultra-sensitive assays. If, or how, haemodialysis influences troponin is still under debate. Failure to interpret troponin values correctly during dialysis may lead to overlooked AMI´s thus putting patients' lives at risk. The aim of this systematic review is to examine the literature regarding the effect hemodialysis has on hs-cTnI. METHOD: A systematic review was performed. Inclusion criteria: measurement of hs-cTnI before and after dialysis in asymptomatic patients. Full text articles only were eligible. Exclusion criteria: posters, abstracts and articles in other languages than English. JK and MH screened 1745 publications. In cases of conflict, FB was contacted as a referee. A total of 153 articles were eligible for full text screening. The Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS2) score was used in terms of risk of bias and quality assessment. RESULTS: Seven articles met the inclusion criteria (see Table 1 ). The sample size of the included studies ranged from n = 13 to n =100 and n =310 in total. Two articles investigated exclusively ultra-sensitive cTnI. One article examined both ultra-sensitive cTnI and hs-cTnI. Three articles examined the effect of haemodiafiltration (HDF) on hs-cTnI. In general, dialysis modalities were rarely described in detail. Only one article showed an increase in hs-cTnI after four hours haemodialysis (HD)/haemodiafiltration (HDF); however, hs-cTnI decreased significantly after 8 h. One study showed no change in the control group in patients who were exposed to remote ischemic preconditioning, although, a statistically insignificant 10% change in the background population was displayed. Of the studies that found a decrease in hs-cTnI, the range was from –3.4% to –36% with a significant decrease in four studies after 4 h HD/HDF. Hs-cTnI concentrations were corrected differently in three articles using either haematocrit concentration, total protein and albumin, or weight change after dialysis. Corrections might make sense in the trial setting, but pose a challenge regarding how to interpret troponin after dialysis in real life, where blood samples are not corrected following dialysis. The use of mean, median and different concentration corrections made sub-analysis and meta-analysis impossible. CONCLUSION: Most publications included in the review showed a decrease of hs-cTnI after dialysis. Diagnosing AMI is based on typical symptoms, signs of ischemia in the ECG and a significant change of troponin (cTn) with at least one value above the 99th percentile. A decrease of hs-cTnI during HD/HDF can alter the diagnostic validity of troponin. The level of significance of the decreased troponin is influenced by sample size, which was low in general. However, it is very important to underline that one size does not fit all. Further studies with larger sample sizes are needed for sub-analysis for gender and age. Additionally, dialysis details could impact the outcome of the influence of haemodialysis on troponin.